2014
DOI: 10.15517/rbt.v62i3.14064
|View full text |Cite
|
Sign up to set email alerts
|

Ecotourism and primate habituation: Behavioral variation in two groups of white-faced capuchins (Cebus capucinus) from Costa Rica

Abstract: Abstract:The increase of ecotourism operations within Costa Rica during the last 20yrs has brought more and more humans into close, direct contact with several wildlife species. One of these species is the white-faced capuchin (Cebus capucinus), highly gregarious, and with exposure over time, willing to come into close vicinity of humans and their developments. Such contact has its advantages and disadvantages for the ecotourism industry. We observed white-faced monkeys in order to assess the impact of human p… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
1

Citation Types

0
4
0

Year Published

2019
2019
2024
2024

Publication Types

Select...
7
1

Relationship

0
8

Authors

Journals

citations
Cited by 8 publications
(4 citation statements)
references
References 10 publications
0
4
0
Order By: Relevance
“…Understanding how white-faced capuchins utilize human resources is a key step in being able to manage and prevent conflict between humans and monkeys where park visitors have the opportunity to interact with wild monkeys. Preventing escalating monkey-human conflicts over human-sourced food is essential not only to protect the integrity of the local ecosystem and health of the monkey population but to ensure a truly sustainable ecotourism economy (Krüger, 2005;Webb and McCoy, 2014). Our results suggest that monkeys in MANP in our 2008-2009 study period initiated the majority of interactions to access human food.…”
Section: Discussionmentioning
confidence: 74%
“…Understanding how white-faced capuchins utilize human resources is a key step in being able to manage and prevent conflict between humans and monkeys where park visitors have the opportunity to interact with wild monkeys. Preventing escalating monkey-human conflicts over human-sourced food is essential not only to protect the integrity of the local ecosystem and health of the monkey population but to ensure a truly sustainable ecotourism economy (Krüger, 2005;Webb and McCoy, 2014). Our results suggest that monkeys in MANP in our 2008-2009 study period initiated the majority of interactions to access human food.…”
Section: Discussionmentioning
confidence: 74%
“…Interactions between humans and capuchins tend to be pacific, in general (Nunes et al, 2021), although high rates of conflict have been recorded in some scenarios, where capuchins are in almost constant contact with humans (e.g. Dos Santos & Martinez, 2015; Shasta E. Webb, 2014). In 2014, Sacramento (2014) found that 46% of the interactions between capuchins and visitors in the BNP were conflictual, while we recorded an even higher rate–60.6%–in the same study area.…”
Section: Discussionmentioning
confidence: 99%
“…Carder et al (2018) observed during their study of sloth selfie tourism that other species were available as tourist photo props including "common caiman, green anaconda, and to touch free-ranging baited squirrel monkeys, various parrot species and toucans" (4). Primates especially are a major draw for wildlife selfies and encounters with tourists (McKinney, 2014;Negrín, Fuentes, Espinosa, & Dias, 2016;Webb & McCoy, 2014), and research around the impacts of tourists on macaques in both African and Asian contexts have uncovered the potential risks of zoonoses, increased aggression and poaching generated by such attractions (Brotcorne et al, 2017;Hsu, Kao, & Agoramoorthy, 2009;Maréchal, Semple, Majolo, & MacLarnon, 2016;Maréchal et al, 2011;Schmidt-Burbach, Ronfot, & Srisangiam, 2015;Stazaker & Mackinnon, 2018).…”
Section: 'Wild' Selfies and Tourismmentioning
confidence: 99%